LEGAL REVIEW OF THE REFUND PROCEDURE IN CASES OF FAILURE TO PAY A LAND SALE-PURCHASE DEED IN A LAWSUIT ORIGIN OF DEBT AND RECEIVABLE (Court Decision Study Number: 760/Pdt.G/2023/PN.Mdn) - Reza Ananda Syahputra; Henry Aspan; Siti Nurhayati (CV. RADJA PUBLIKA, 2025)
The land sale and purchase deed serves as authentic evidence in business transactions protected by civil law, as regulated in Article 37 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration, which states that this deed is the basis for registering the transfer of rights at the Land Office. However, in practice, disputes often occur due to a lack of clarity in the agreement, violation of the agreement, or one of the parties failing to fulfill its obligations. In the case of Decision No. 760/Pdt.G/2023/PN.Mdn, the dispute arose when the plaintiff requested a refund for a land sale and purchase transaction that initially involved debts and land certificate guarantees. This case is important to analyze, especially in the context of civil law regarding the formal and substantive requirements of civil lawsuits. The formulation of the problem in this study is What is the legal procedure for refunding funds in cases of default on land sale and purchase deeds, What are the legal considerations of the court in assessing the lawsuit filed by the plaintiff, Is the judge's decision in Decision No. 760/Pdt.G/2023/PN.Mdn has provided adequate legal protection for the parties involved. This research was conducted using a descriptive approach with qualitative methods with a normative juridical research type based on secondary data sources taken from case studies of court decisions and laws with analysis using related legal materials. The results of the study indicate that the plaintiff's claim in this case is declared vague (obscuur libel) because the posita and petitum are unclear, and there is a lack of written evidence supporting the plaintiff's claim. The Panel of Judges also stated that there was an error in determining the defendant (error in persona), so the lawsuit does not meet the formal requirements. To avoid this, the lawsuit must be drafted with a clear posita and petitum, supported by strong evidence, and addressed to the appropriate defendant. By fulfilling the formal and substantive requirements, the lawsuit can be deemed not vague and has a chance of being accepted in court.